2013
DOI: 10.7314/apjcp.2013.14.9.5473
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Basic Laboratory Methods in Non-Small-Cell-Lung Cancer

Abstract: Background: In our study, the LDH, albumin, hemoglobin, neutrophile, thrombocyte, lymphocyte counts and prognostic significance of neutrophile-lymphocyte and thrombocyte-lymphocyte ratios in NSCLC derived from these counts obtained during regular examinations of patients were examined. Materials and Methods: Histopathologically diagnosed non-small-cell-lung cancer patients between 2008 and 2010 were included in the study. Before the treatment, full blood count including routine lymphocyte count, blood biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…al and Vildan Kaya et. al reported that pretreatment NLR measurements can predict patient prognosis in NSCLC patients (Kaya et al, 2013, Unal et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…al and Vildan Kaya et. al reported that pretreatment NLR measurements can predict patient prognosis in NSCLC patients (Kaya et al, 2013, Unal et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…(Gabay et al, 1999;Mantovani et al, 2008;Yildirim et al, 2013). In several studies, high inflammatory parameters (CRP, alpha and gamma globulins, neutrophil lymphocyte ratio (NLR), complement C3-C4) were found and associated with reduced overall survival in patients with different cancers including lung cancers (Shimada et al, 2003;Canna et al, 2005;Kaya et al, 2013;Zheng et al, 2013;Dai et al, 2014;Soliman et al, 2014). Increasing synthesis of acute phase proteins and interleukins and tumor necrosis-related hypoxia may be the mechanisms underlying this increased inflammation (McMillan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After that, emerging evidences from several studies have pointed out that NLR has a prognostic value in patients with pancreatic (Aliustaoglu et al, 2010), breast (Azab et al, 2012), lung (Kaya et al, 2013;Unal et al, 2013) and gastric (Jung et al, 2011) cancers. Recent literature has relatively fewer papers that focused on the significance of the pre-treatment NLR in CRC.…”
Section: Discussionmentioning
confidence: 99%